The early phase change Gene in Maize - Vega, Shifra H. (American Society of Plant Biologists, 2002)
Recessive mutations of the early phase change (epc) gene in maize affect several aspects of plant development. These mutations were identified initially because of their striking effect on vegetative phase change. In certain genetic backgrounds, epc mutations reduce the duration of the juvenile vegetative phase of development and cause early flowering, but they have little or no effect on the number of adult leaves. Except for a transient delay in leaf production during germination, mutant plants initiate leaves at a normal rate both during and after embryogenesis. Thus, the early flowering phenotype of epc mutations is explained completely by their effect on the expression of the juvenile phase. The observation that epc mutations block the rejuvenation of leaf primordia in excised shoot apices supports the conclusion that epc is required for the expression of juvenile traits. This phenotype suggests that epc functions normally to promote the expression of the juvenile phase of shoot development and to suppress the expression of the adult phase and that floral induction is initiated by the transition to the adult phase. epc mutations are epistatic to the gibberellin-deficient mutation dwarf1 and interact additively with the dominant gain-of-function mutations Teopod1, Teopod2, and Teopod3. Genetic backgrounds that enhance the mutant phenotype of epc demonstrate that, in addition to its role in phase change, epc is required for the maintenance of the shoot apical meristem, leaf initiation, and root initiation.